PENINGKATAN SIKAP DISIPLIN DAN HASIL BELAJAR PERKALIAN MENGGUNAKAN PMRI KELAS II SDK SANG TIMUR YOGYAKARTA - Rizky, Ariana; Sumarah, Ignatia Esti (Pusat Pengembangan Pendidikan dan Penelitian indonesia (P4I), 2025)
Based on the results of the researcher’s observations through direct observation in the classroom and interviews with the homeroom teacher of Grade II B at SDK Sang Timur Yogyakarta, it was found that students were not yet fully consistent in their disciplinary attitudes during the learning process. In addition, in the mathematics learning outcomes on multiplication material, several students had not yet reached the Minimum Mastery Criteria (KKTP) of 70. Therefore, the researcher conducted Classroom Action Research (CAR) by applying several methods such as observation and interviews, documentation study, and tests. The research subjects were all students of Grade II B, consisting of 12 girls and 4 boys. The Classroom Action Research (CAR) was carried out in two cycles using the PMRI (Pendidikan Matematika Realistik Indonesia) approach along with contextual tools and media. This showed an increase in the percentage of disciplinary attitudes: the